2021
DOI: 10.3233/cbm-200006
|View full text |Cite
|
Sign up to set email alerts
|

LCP1 is a prognostic biomarker correlated with immune infiltrates in gastric cancer

Abstract: BACKGROUND: Previous studies have identified LCP1 as a diagnostic and prognostic marker in several cancers. However, the role of LCP1 in gastric cancer (GC) and its effect on tumor immune infiltration remain unclear. OBJECTIVE: The aim was to explore the role of LCP1 in GC and its effect on tumor immune infiltration. METHODS: We explored the expression of LCP1 relative to clinicopathology in GC patients by bioinformatics analysis and immunohistochemistry. Using cBioportal database, we analyzed the characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Ge et al [ 42 ] discovered that LCP1 promotes osteosarcoma progression via the activation of the JAK2/STAT3 signaling pathway. Zeng et al [ 43 ] reported that several immune marker sets were highly correlated with LCP1, which was associated with tumor-infiltrating lymphocytes in gastric cancer. In macrophages, LCP1 is required for podosome formation and function [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ge et al [ 42 ] discovered that LCP1 promotes osteosarcoma progression via the activation of the JAK2/STAT3 signaling pathway. Zeng et al [ 43 ] reported that several immune marker sets were highly correlated with LCP1, which was associated with tumor-infiltrating lymphocytes in gastric cancer. In macrophages, LCP1 is required for podosome formation and function [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its hub genes including LCP1, ACAP1, CCL19, CD3E, HLA-DRA, C1QA and CORO1A, were strongly associated with activities of immune cells. LCP1 was related to tumor infiltrating lymphocytes and plays an important role in lymphocyte formation and anti-cancer immune response [ 16 ]. The high expression of ACAP1 is positively associated with a variety of immune-related biological processes and pathways, such as adaptive immune response, T cell activation, and macrophage activation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocyte cytosolic protein 1 (LCP1) is L-plastin or leukocyte-specific plastin (17) targeted by lncRNA Maclpil (12). LCP1 plays a curtail role in immune responses by regulating cell adhesion, migration, and activation (12,18,19). LCP1 also affects cell fate.…”
Section: Discussionmentioning
confidence: 99%